The Role and Responsibility of the University Library in Publishing in a University - Savenije, Bas; Grygierczyk, Natalia (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
As a consequence of developments in information technology, the traditional information chain is subject to change: the separate functions in this chain become more and more integrated and the roles played by the traditional parties are most uncertain. Several new models in scholarly publishing and communication are emerging, in which the scientific community and the scientists themselves play a central role. It is more than natural for universities to support these developments in order to realise new models of scientific communication that are more in tune with the needs of the academic community than the traditional model, which has led to a serious serials crisis. An important step in this direction is that each university encourages scientists to make more use of ICT in their research publications. However, it is also necessary to give serious attention to organisational matters: in this respect every university should take responsibility for collecting, archiving and disclosing the scientific output of its own scientists. The provision of scientific information is the traditional core business of university libraries and it is a natural extension of this role for university libraries to support this development and to organise the processes needed. The paper describes the role that universities and their libraries have to play. It also gives some examples of library initiatives in this field, including an evaluation of their impact on the innovation of scientific communication.